Nutritional diagnoses in people with type 2 diabetes: association with metabolic, anthropometric, and dietary parameters - Landa-Anell, María Victoria; Del Razo-Olvera, Fabiola M.; Bodnar, Irene; Cordova-Isidro, Brenda; Lagunas-Valdepeña, Daniela; Arias-Marroquín, Ana T.; García-Ulloa, Ana Cristina; Melgarejo-Hernández, Marco Antonio; Hernández-Jiménez, Sergio; , for the Group of Study CAIPaDi (Frontiers in Nutrition, 2024)
Background: Nutritional diagnosis involves identifying a nutritional problem, its cause, and the signs that indicate it to guide appropriate treatment. Few studies report on the most prevalent nutritional diagnoses in people living with type 2 diabetes (T2D).Objective: To define nutritional diagnoses across different domains and their association with metabolic, anthropometric, and dietary parameters in individuals with T2D.Methods: A personalized nutritional intervention was conducted using the Nutrition Care Process (NCP) model, which encompasses assessment, diagnosis, intervention, and evaluation, utilizing standardized terminology from the Nutrition Care Process Terminology (NCPT). Two dietitians, trained and standardized in applying the NCP and NCPT, performed patient assessments and established the diagnoses. Patients over 18 years old with a diagnosis of T2D for less than five years were included.Results: Data from 2,050 patients were analyzed, of whom 55.3% were women, and 44.7% were men, with a median age of 57 and 54 years, respectively. The most prevalent nutritional diagnosis was excessive energy and carbohydrate intake. Diagnoses were distributed across domains: Intake (55.9%), Behavioral/Environmental (32.7%), Clinical (10.2%), and 1.2% without nutritional diagnosis. Significant intergroup differences were observed in anthropometric variables such as BMI, waist circumference, and body fat percentage (p<0.05). HbA1c and glucose levels were significantly higher in the Intake and Behavioral groups (p<0.001). ACR was higher in the ingestion group (p=0.007). Caloric and carbohydrate intake were higher in the ingestion group, while protein and fat intake were higher in the clinical and behavioral groups (p < 0.001).Nutritional diagnoses in the Intake domain, followed by Behavioral/Environmental and Clinical domains, are highly prevalent in people with T2D and are associated with worse metabolic control, higher BMI, and increased energy and carbohydrate intake. Timely identification of issues in these domains can support targeted nutritional therapy to improve disease management and promote a healthy lifestyle.Abbreviations: Medical nutrition therapy (MNT), Nutrition Care Process (NCP), Nutrition Care Process Terminology (NCPT). Clinical Trial Registry number and website where it was obtained: (https://clinicaltrials.gov/study/NCT02836808?term=caipadi&rank=2 (NCT02836808))